2011
DOI: 10.1021/jo201469b
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure and Dynamics of Duplex GNA

Abstract: Glycol nucleic acid (GNA), with a nucleotide backbone comprising of just three carbons and the stereocenter derived from propylene glycol (1,2-propanediol), is a structural analog of nucleic acids with intriguing biophysical properties, such as formation of highly stable antiparallel duplexes with high Watson-Crick base pairing fidelity. Previous crystallographic studies of double stranded GNA (dsGNA) indicated two forms of backbone conformations, an elongated M-type (containing metallo-base pairs) and the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Especially for SNA, preorganization of the single strand is unlikely because both SNA/ a TNA and a TNA/ a TNA duplexes have almost the same CD spectra (Figure 5). Recently, Wiest and co‐workers suggested that the conformational flexibility inherent to a duplex of GNA also contributed to the decrease in entropy loss 26. However, because a TNA and SNA duplexes were not stabilized by the decrease in entropic loss like GNA but rather large enthalpic predilection, conformational flexibility is less important in these nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for SNA, preorganization of the single strand is unlikely because both SNA/ a TNA and a TNA/ a TNA duplexes have almost the same CD spectra (Figure 5). Recently, Wiest and co‐workers suggested that the conformational flexibility inherent to a duplex of GNA also contributed to the decrease in entropy loss 26. However, because a TNA and SNA duplexes were not stabilized by the decrease in entropic loss like GNA but rather large enthalpic predilection, conformational flexibility is less important in these nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wiest and co-workers suggested that the conformational flexibility inherent to a duplex of GNA also contributed to the decrease in entropy loss. [26] However, because aTNA and SNA duplexes were not stabilized by the decrease in entropic loss like GNA but rather large enthalpic predilection, conformational flexibility is less important in these nucleic acids. Flexibility of the scaffold should result in an entropic penalty relative to DNA and RNA duplexes.…”
Section: Discussionmentioning
confidence: 99%
“…In the GNA family, the ( S )- and ( R )- enantiomers do not pair with each other and a structure for ( R )-GNA has not yet been reported. Nevertheless, the structure of ( S )-GNA provides a number of interesting observations that include cross-strand base stacking as opposed to the more common intrastrand base stacking and a strong hydrophobic effect from the 2′-methylene group ( 73 75 ). PNA is capable of forming a stable antiparallel duplex and can also cross-pair efficiently with DNA and RNA.…”
Section: Xna Pairing Modesmentioning
confidence: 99%
“…More recently, the use of a simpler sugar, glycol, has been studied. It has been shown that the corresponding glycolic nucleic acid can form helical molecules, opening the possibility of a world of GNA (Chen et al 2009;Johnson et al 2011). Even a living world chemically closer to LUCA, but with the involvement of amyloid: an ANA world (amyloid nucleic acid) with nucleic acids bound to the amyloid protein has been considered .…”
Section: Life (Somewhat) Close To Life As We Know Itmentioning
confidence: 99%